Hubungan antara Self-Esteem dan Interpersonal Competence Mahasiswa Psikologi Angkatan 2017-2019 di Universitas X Bandung - Vivid Nurny Murdyne; Endeh Azizah (Universitas Kristen Maranatha, 2022)
This study aims to determine the relationship between self-esteem and interpersonal competence in psychology students. Participants in this research were 194 students which consisted of students from class of 2017-2019 faculty of psychology at “X” University Bandung. Each participant filled out self-esteem and interpersonal competency questionnaires with high-reliability values. Through the Spearman Rank correlation test, the results show a relationship between self-esteem and Interpersonal Competence. This result means that students who judge themselves can regulate and control their behavior and influence others, assess themselves as valuable and meaningful, successfully fulfill moral principles, and meet achievement demands can establish warm interpersonal relationships with others. Therefore, the faculty can help students maintain and improve their interpersonal competence. With this competency, they can have a life of harmonious social relations that support their success in the study process.